Clinical Applications of 980 nm Diode Laser for Soft Tissue Procedures in Prosthetic Restorative Dentistry - Gupta, Abhishek; Jain, Niharika; Makhija, Permanand Garebdas (Journal of Lasers in Medical Sciences, 2012)
The purpose of these case reports is to analyze the results of gingivectomy and gingival troughing to determine the evidence on the effectiveness of laser-assisted soft tissue procedures and soft tissue management in aesthetic dentistry.The patients in these case reports underwent 980 nm diode laser assisted gingivectomy and gingival troughing to achieve immediate hemostasis and moisture control, adjunctive to the aesthetic restoration of the carious lesion and prosthetic rehabilitation of the posterior tooth.Successful healing of gingival tissues has been observed after 15 days in both cases. Also, laser assisted gingival tissue management allowed the operator to finish and polish the restoration on the same day.The ability of soft tissue lasers to control moisture and facilitate hemostasis appears particularly promising for clinicians excising gingival tissue, and using resective techniques for gingival troughing. Treatment with a dental laser ensures a successful aesthetic procedure with proper tissue form, function and biocompatibility.